2021
DOI: 10.15244/pjoes/133720
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Riparian Vegetated Filter Strips in Removing Agricultural Nonpoint Source Pollutants in Agricultural Runoff from the Liao River Area, China

Abstract: Riparian vegetated filter strips (RVFS) can effectively intercept agricultural non-point source pollution (ANSP) into a water body and reduce the risk of water body pollution. The present study evaluates the long-term effectiveness of different types and lengths (5 m, 9 m, 13 m) of RVFS in reducing the suspended solids (SS) and nutrients from agricultural runoff. Three field experimental plots (T1-T2-T3) planted with weeds, sweet clover (Melilotus suaveolens L.) and sweet clover/Chinese wingnut (Pterocarya ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The literature suggests that VFS may struggle to reduce the movement of more total dissolved forms of N (e.g., nitrate) and P into surface waters, although relatively high trapping efficiencies have been reported for these forms (Yang et al, 2015). In a recent study, Tang et al evaluated the long-term effectiveness of different types and lengths of VFS in reducing suspended solids and nutrients in agricultural runoff (Tang et al, 2021). They found that VFS (9 m, 13 m) reduced suspended solids to 79% and 84% of the original amount, in consistence with the findings of the present study.…”
Section: Effect Of Rb-prb With Vfs On Nitrogen Loss From Sloping Farm...mentioning
confidence: 99%
See 1 more Smart Citation
“…The literature suggests that VFS may struggle to reduce the movement of more total dissolved forms of N (e.g., nitrate) and P into surface waters, although relatively high trapping efficiencies have been reported for these forms (Yang et al, 2015). In a recent study, Tang et al evaluated the long-term effectiveness of different types and lengths of VFS in reducing suspended solids and nutrients in agricultural runoff (Tang et al, 2021). They found that VFS (9 m, 13 m) reduced suspended solids to 79% and 84% of the original amount, in consistence with the findings of the present study.…”
Section: Effect Of Rb-prb With Vfs On Nitrogen Loss From Sloping Farm...mentioning
confidence: 99%
“…Vegetated filter strips (VFS), designated areas of land intended to create a buffer between agricultural land and ecologically significant aquatic or terrestrial environments. They demonstrated efficacy in intercepting agricultural non-point-source pollution before it enters a water body (Prosser et al, 2020;Tang et al, 2021). Research consistently demonstrates that VFS can efficiently capture a substantial portion of the total phosphorus and nitrate load in field runoff, preventing its entry into surface water (Janssen et al, 2018;Lyu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%